Validation of Online Prognostication Model that Predicts Survival for Women with Early Breast Cancer in Egypt - Gehan A. Khedr; Sarah Salah; Nadia A Abd El Moneim; Nashaat S Lotfy (Asian Pacific Journal of Cancer Care, 2020)
Introduction: Breast Cancer is estimated to be the most common female cancer in Egypt. The decision on adjuvant therapy in early breast cancer is complex and requires many considerations. PREDICT is an online prognostication tool for early breast cancer. It was first revealed in 2011 and it has been widely used. This study aimed to illustrate the applicability of this model on Egyptian patients. Methods: This study included 128 female patients treated for early breast cancer with surgery and adjuvant therapy in Alexandria, Egypt in 2005 to validate the efficacy of PREDICT as an online prognostication model to estimate survival in those patients. Patients’ data were obtained from the archives of the Department of Clinical Oncology, Faculty of Medicine, and the Department of Cancer Management and Research, Medical Research Institute, University of Alexandria, Egypt. Patients’ data were manually entered into the prognostication model and the predicted survival results obtained were compared to the actual survival of study patients. Results: The predicted number of survivors after 5 years in the entire cohort was 125 (97.7%) compared to 123 (96.1%) actual survivors. The difference was 1.6% which was not significant (p= 0.625). The predicted number of survivors after 10 years in the entire cohort was 77 (60.2%) compared to 81 (63.3%) actual survivors. The difference was -3.1% which was not significant (p= 0.671). Conclusion: PREDICT accurately predicts 5-year and 10-year OS in the entire study population. This validates the use of this online model to aid in the decision as regard systemic therapy.